1960
DOI: 10.5254/1.3542153
|View full text |Cite
|
Sign up to set email alerts
|

The Action of Binary Accelerator Systems of Vulcanization

Abstract: 1. It was established that in the joint use of vulcanization accelerators there takes place mutual activation of the accelerators, activation of one accelerator or additive action depending on the chemical structure of the accelerators. 2. Of the studied combinations of vulcanization accelerators the systems showing mutual activation are disulfides or mercaptans with nitrogen containing organic bases, and disulfides with sulfenamides. Sulfenamides with nitrogen containing organic bases result in activation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Frequently, the use of two or more accelerators simultaneously, instead of a single one, has been found to be more advantageous for technological applications, since these mixed systems generally exhibit higher vulcanization activity (synergism) than the individual accelerators separately. Significant contribution with respect to mutual activity of the binary systems of accelerators during the vulcanization of NR has been made by Dogadkin and co-workers [3], Skinner and Watson [2], Kempermann [1] and Krymowski and Taylor [4]. Debnath et al [5,6] have also made some studies in this regards in the recent past.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, the use of two or more accelerators simultaneously, instead of a single one, has been found to be more advantageous for technological applications, since these mixed systems generally exhibit higher vulcanization activity (synergism) than the individual accelerators separately. Significant contribution with respect to mutual activity of the binary systems of accelerators during the vulcanization of NR has been made by Dogadkin and co-workers [3], Skinner and Watson [2], Kempermann [1] and Krymowski and Taylor [4]. Debnath et al [5,6] have also made some studies in this regards in the recent past.…”
Section: Introductionmentioning
confidence: 99%
“…The physical and chemical properties of the vulcanizates depend on the type of the accelerators used and also on the condition of vulcanization. Frequently, the use of two or more accelerators simultaneously, instead of a single one, are found to be more advantageous for technological applications, as these mixed systems generally show higher vulcanization activity (synergism) than the individual accelerators separately . Mixed accelerator systems have, therefore, gathered much attention both from scientific and technical points of view.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that in a binary accelerator system, the interaction between the accelerators produce reactive compounds, which decompose into free radicals or ions, capable of initiating a reaction between sulfur, rubber and crosslinking process of the latter . Significant contribution with respect to synergistic activity of the binary systems of accelerators during vulcanization of natural rubber (NR) are revealed by Dogadkin et al, Skinner and Watson, Kempermann and Redetzky, and Krymowsky and Taylor. Debnath and Basu also have made some investigations in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…These observations are in accordance with the work by Dogadkin et al, who established that the combined action of accelerators as disulfides (TMTD) or mercaptans (MBT) with nitrogen containing organic bases (Sulfads) takes place by mutual activation of the accelerators. 25 The results may be credited to a large amount of cross-links ( Figure 2) which provide a network strong enough to stand the applied deformations.…”
Section: Resultsmentioning
confidence: 97%